Effect of boric acid on the growth and production of β-glucosidase in Paecilomyces variotii - Ang, Swi See; Salleh, Abu Bakar; Abu Bakar, Fatimah; Yusof, Nor Azah; Zaman, Muhammad Zukhrufuz; Lee, Yook Heng (Academic Journals, 2011)
Boric acid was examined for antifungal activity against several species of fungi. The growth and production of β-glucosidase in several strains of fungi were tested in the media containing various concentrations of boric acid. The results indicated that the growth of Trichoderma strains was reduced with increasing amount of boric acid up to 0.3% (w/v). However, Paecilomyces variotii was able to tolerate boric acid above 0.3% (w/v) by increasing its growth. Trichoderma also showed low production of β-glucosidase as compared to P. variotii. Present study revealed that boric acid works as effective fungicide by inhibiting the production of β-glucosidase and the growth of fungi. This suggests that boric acid might be useful for the treatment of fungal infection caused by P. variotii or Trichoderma strains.